An Artificial Nerve Capable of UV‐Perception, NIR–Vis Switchable Plasticity Modulation, and Motion State Monitoring. Issue 1 (29th October 2021) - Ni, Yao; Feng, Jiulong; Liu, Jiaqi; Yu, Hang; Wei, Huanhuan; Du, Yi; Liu, Lu; Sun, Lin; Zhou, Jianlin; Xu, Wentao
Abstract: The first flexible organic‐heterojunction neuromorphic transistor (OHNT) that senses broadband light, including near‐ultraviolet (NUV), visible (vis), and near‐infrared (NIR), and processes multiplexed‐neurotransmission signals is demonstrated. For UV perception, electrical energy consumption down to 536 aJ per synaptic event is demonstrated, at least one order of magnitude lower than current UV‐sensitive synaptic devices. For NIR‐ and vis‐perception, switchable plasticity by alternating light sources is yielded for recognition and memory. The device emulates multiplexed neurochemical transition of different neurotransmitters such as dopamine and noradrenaline to form short‐term and long‐term responses. These facilitate the first realization of human‐integrated motion state monitoring and processing using a synaptic hardware, which is then used for real‐time heart monitoring of human movement. Motion state analysis with the 96% accuracy is then achieved by artificial neural network. This work provides important support to future biomedical electronics and neural prostheses. Abstract : The first flexible organic‐heterojunction neuromorphic transistor (OHNT) that senses broadband light, including near‐ultraviolet (NUV), visible (vis), and near‐infrared (NIR), and processes multiplexed‐neurotransmission signals is designed. This provides new path to artificial nervous system with enriched functionalities and potentially applicable to bioinspired and biointegrated electronics.